Addressing the Silent Epidemic of Hepatitis B Virus: Awareness, Screening and Vaccination Efforts in Abuja, Nigeria - Mrs Ogechukwu Akabuike; Dr Mabel Aworh; Ms Nkiruka Uzoebo; Dr Kenneth Enwerem; Mr John Ewart; Pharm Onyinye Agukwe; Pharm Kingsley Ngong; Dr Amos Dangana; Dr Idris Abdullahi (International Journal of Infectious Diseases, 2025)
Introduction: Hepatitis B virus (HBV) is a major global health threat, especially in Sub-Saharan Africa, where Nigeria has a prevalence exceeding 8%. Despite the availability of effective vaccines, inadequate coverage and lack of awareness have resulted in high rates of chronic infections and HBV-attributable liver disease. The study aimed to raise awareness of HBV across various communities and to enroll participants for HBV screening and vaccination. Methods: A cross-sectional study was conducted in 16 districts of Abuja from April 2022 to March 2023. Participants aged 18 and over were screened for hepatitis B, and those testing negative were offered on-site vaccination. Blood samples were collected and tested using HBV immunochromatographic tests and real-time polymerase chain reaction (RT-PCR) for HBV DNA quantification. Data were collected through interviews and analyzed using R software, with descriptive statistics calculated for continuous and categorical variables. Associations between socio-demographic factors and hepatitis B/vaccine status were assessed using the Chi-square test of independence. Results: Out of 3,245 individuals screened, 141 (4.3%) tested positive for HBV. The highest prevalence was observed in the 20–39 age group (5.9%), with males showing a higher infection rate (5.4%) compared to females (3.7%) [p = 0.02]. The mean age of HBV-positive individuals was significantly lower (30.8 years) than those negative for HBV (36.2 years) [p = <0.001]. Among 2,506 participants who consented to vaccination, 2,488 received the first dose, 1,834 the second dose (73.2%), and 1,100 the third dose (43.9%). Vaccination uptake declined with each subsequent dose, but higher proportions of older participants completed the third dose. A similar pattern of HBV prevalence was observed across gender and age groups. Discussion: This study shows a significant sociodemographic differences in HBV prevalence, with a rate of 4.3% in underprivileged areas, which is greater than Lagos' 2.1%. Risk variables such as proximity to IDP camps and age-related behaviours contributed to the discrepancy. While 80.2% received the initial vaccine dosage, just 35.4% completed the third. Barriers such as financial constraints highlight the importance of targeted treatments, immunisation, and education in controlling HBV spread, particularly among high-risk populations. Conclusion: The study reveals a 4.3% prevalence of hepatitis B, with the highest infection rate among individuals aged 20–39 years, and males showing a higher prevalence than females. Although vaccination uptake was high for the first dose, adherence declined for subsequent doses. These findings highlight the need for targeted public health interventions, particularly among younger adults and males, to improve awareness and vaccination completion. Enhanced community engagement and sustained vaccination efforts are crucial for reducing HBV transmission and achieving better coverage.